SELF-REGULATED LEARNING DESIGN AS AN APPLICATION OF STUDENT'S SELF-ASSESSMENT IN MATHEMATICS LEARNING - Nabila Nurhaliza Ali (USN Kolaka, 2024)
Self-regulated learning is one of the important factors in learning to control oneself in thinking and acting. The purpose of this research is to analyze how much students have achieved their independence in learning. Student learning independence includes all matters of student learning independently without the help of others, student learning motivation or things that affect student independence in learning, especially in learning mathematics. This analysis study will be continued as an effort to improve self-regulated learning. The scope of self-regulated learning was analyzed by descriptive quantitative method through data collection techniques in the form of questionnaires on the object of research taken from a population of 25 students. Data collection was carried out with a questionnaire consisting of 20 statements from indicators of students' self-regulated learning ability. In learning mathematics, students who have initiative and instrinsic learning motivation, apply learning targets, and set a learning schedule in the percentage of almost half of the students do according to these indicators of independence. Almost all students diagnose learning needs, view difficulties as challenges, utilize and seek relevant sources. However, a small proportion of students lack self-efficacy or confidence in their abilities and are still low in evaluating the learning process and results. So that as an educator this needs to be considered to be able to improve students' self-regulated learning abilities (learning independence) in order to improve student achievement.